Suspension of Esophageal Stent: An Endoscopic Technique for the Treatment of Esophagopleural Fistula - Zheng, Chunsi; Yang, Jingbo (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Zheng C, Yang J. Suspension of esophageal stent: An endoscopic technique for the treatment of esophagopleural fistula. Turk J Gastroenterol. 2024;35(5):418-420.